The wasp Flacopimpla varelae Gauld (Ichneumonidae: Pimplinae), parasitoid of the spider Achaearanea tingo Levi (Theridiidae: Theridiinae), with description of the male wasp - Sobczak, Jober Fernando; Villanueva-Bonilla, German Antonio; Pádua, Diego Galvão De; Messas, Yuri Fanchini (Zootaxa, 2017)
Parasitoid organisms can manipulate the morphology, physiology and/or behavior of their hosts to increase their own survival (Moore 2002; Korenko et al. 2015a). Wasps of the Polysphincta genus-group sensu Gauld & Dubois, 2006 (hereafter polysphinctine wasps) are well known to act exclusively as koinobiont ectoparasitoids of spiders (Gauld & Dubois 2006). The host range of these wasps is remarkably narrow and often species-specific; individuals of some polysphinctine genera (e.g. Hymenoepimecis, Acrotaphus) usually attack orb-weaver spiders (Pádua et al. 2016), whereas other are specialized on spiders that construct three-dimensional webs. Fritzén (2014), for example, discussed that Oxyrrhexis Föerster, 1869, Zatypota Föerster, 1869 and Flacopimpla Gauld, 1991 are specialized on theridiid hosts, the last two mainly or exclusively on spiders of the subfamily Theridiinae.